Urea Transporter Physiology Studied in Knockout Mice - Li, Xuechen; Chen, Guangping; Yang, Baoxue (Frontiers in Physiology, 2012)
In mammals, there are two types of urea transporters (UTs), UT-A and UT-B. The UT-A transporter is mainly expressed in kidney epithelial cells; while UT-B demonstrates a broader distribution in kidney, heart, brain, testis, urinary tract and other tissues. Over the past few years, multiple UT knockout mouse models have been generated enabling us to explore the physiological roles of the different UTs. In the kidney, deletion of UTA1/A3 results in polyuria and a severe urine concentrating defect, indicating that intrarenal recycling of urea plays a crucial role in the overall capacity to concentrate urine. Since UT-B has a wide distribution, multiple phenotypic abnormalities were found in UT-B null mice, such as defective urine concentration, heart block with aging, depression-like behavior and earlier male sexual maturation. This review summarizes the new insights of urea transporter functions in different organs from UT knockout mice. Finally, we take a glance at the pharmacological prospect of UTs.